PERAN ULAMA AL WASHLIYAH DALAM PENGEMBANGAN ILMU AGAMA - Ja'far, Ja'far (Islamijah: Journal of Islamic Social Sciences, 2021)
Abstrak: Ulama sebagai kelompok elit dalam komunitas Muslim telah memberikan kontribusi bagi pengembangan pemikiran Islam di Nusantara terutama dengan menghasilkan karya-karya keislaman dalam berbagai bidang. Studi ini bertujuan untuk menelaah peran ulama Al Washliyah dalam pengembangan ilmu agama di Indonesia. Studi ini merupakan studi kepustakaan. Data yang terdiri atas sumber primer dan sekunder dianalisis dengan metode analisis isi. Studi ini mengajukan temuan bahwa ulama-ulama yang mendirikan organisasi Al Washliyah secara aktif mengembangkan ilmu agama di Indonesia. Dalam rangka mengembangkan ilmu agama, mereka menilai penting arti sanad ilmu sehingga sebelum menjadi ulama mereka mengkaji ilmu agama kepada para ulama yang memiliki sanad ilmu yang jelas; menulis dan menghasilkan karya-karya keagamaan dalam berbagai disiplin ilmu; dan mendirikan, termasuk merancang kurikulum, madrasah dan universitas berbasis kitab kuning. Studi ini berhasil melengkapi riset-riset mutakhir tentang peran ulama di Nusantara dalam pengembangan ilmu agama. Kata Kunci: ilmu agama, ulama, Al Washliyah, Nusantara Abstract:Ulama, as an elite group within the Muslim community, have made significant contributions to the development of Islamic thought in the archipelago, particularly through the publication of Islamic books in a variety of subjects. The purpose of this research is to investigate the influence of Al Washliyah's ulama on the development of religious knowledge in Indonesia. This is a research paper on the topic of literature. A content analysis method was used to examine data from both primary and secondary sources. The scholars who created the Al Washliyah group are actively increasing religious knowledge in Indonesia, according to the findings of this research. They assess the importance of the meaning of the chain of knowledge before becoming scholars, so that they can study religious knowledge to scholars who have a clear chain of knowledge; write and produce religious works in various disciplines; and establish, including designing curricula, madrasas, and universities based on the yellow book (kitab kuning). This research successfully complements recent studies on the function of ulama in the development of religious knowledge in the archipelago.Keywords: religious knowledge, ulama, Al Washliyah, Nusantara. Keywords: religious knowledge, ulama, Al Washliyah, Nusantara